IgA (Henoch Schönlein Purpura) Vasculitis in a Pediatric Patient with COVID-19 and Strongyloidiasis - Nakandakari Gomez, Mayron David (2020)
Vasculitis is a rare disease in children, with IgA Vasculitis being its most common presentation. One condition that has been associated with the development of vasculitis is the invasion of the vascular endothelium by Strongyloides stercoralis in cases of hyperinfestation. Another condition that is not yet under-researched is the likely association of IgA vasculitis-like processes with SARS-CoV-2 and COVID-19 infection itself. It is presented the case of a four-year-old patient who healed with palpable purplish lesions to lower limb predominance, acute abdominal pain, and episodes of high digestive hemorrhage. Initially listed as a possible severe dengue and leptospirosis, but clinically and laboratorially associated with IgA vasculitis. It was SARS-CoV-2 IgM and IgG: Reactive. And in parasitological study was identified Strongyloides stercoralis. Symptomatology subsided after administration of corticotherapy and the evolution was favorable.